Why life insurers are key to economic dynamism in Germany - Reint Gropp; William McShane (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2020)
Young entrepreneurial firms are of critical importance for innovation. But to bring their new ideas to the market, these startups depend on investors who understand and are willing to accept the risk associated with a new firm. Perhaps the key reason as to why the US has succeeded in producing nearly all the most successful new firms of the 21st century is the economy's ability to supply vast sums of capital to promising startups. The volume of venture capital (VC) invested in the US is more than 60 times that of Germany (OECD, 2017). In this policy note, we argue that differences in the regulatory and structural context of institutional investors, in particular life insurance companies, is a central driver of the relative lack of VC - and thereby successful startups - in Germany.
Keywords: 330